Perencanaan Komunikasi Pemasaran Kopi Pelipur Lara Selama Pandemi - Anthony Chandra; Muhammad Adi Pribadi (Kiwari, 2023)
Franchising is considered as the most effective business alternative when someone wants to start a career or start a new business. One of them is Kopi Pelipur Lara Banjarmasin which has been affected by the COVID-19 pandemic, especially since the franchise has not been established for 5 years. In this case, marketing communication planning is needed to develop the Pelipur Lara Coffee Franchise business to attract customers. In planning marketing communications, there are important stages in planning integrated marketing communications as a process of promoting a product or service offered. This study aims to analyze the marketing communication planning of Kopi Pelipur Lara during the pandemic. This research uses a case study research method with a qualitative approach obtained through interviews and literature studies. Through this research, it was found that the 5 processes in the marketing communication planning for solace coffee are actively carried out by Kopi solace to attract customers during the pandemic. Waralaba dianggap sebagai sebuah alternatif bisnis yang paling efektif ketika seseorang ingin memulai berkarir atau memulai usaha baru.. Salah satunya adalah Kopi Pelipur Lara Banjarmasin yang terkena imbas dari pandemi covid-19, terlebih waralaba tersebut belum berdiri sampai lima tahun lamanya. Dalam hal ini dalam perencanaan komunikasi pemasaran diperlukan untuk mengembangkan bisnis waralaba Kopi Pelipur Lara untuk menarik pelanggan. Dalam perencanaan komunikasi pemasaran terdapat tahapan penting dalam perencanaan komunikasi permasaran terpadu sebagai proses promosi suatu produk maupun jasa layanan yang ditawarkan. Penelitian ini bertujuan untuk menganalisis perencanaan komunikasi pemasaran Kopi Pelipur Lara selama masa pandemi. Pada penelitian ini menggunakan metode penelitian studi kasus dengan pendekatan kualitatif yang diperoleh dengan wawancara serta studi pustaka. Melalui penelitian ini dihasilkan bahwa lima proses yang ada pada perencanaan komunikasi pemasaran Kopi Pelipur Lara aktif dijalankan oleh Kopi Pelipur Lara untuk menarik pelanggan selama pandemi.